FATIGUE LIFE ANALYSIS OF WING WITH HIGH ASPECT RATIO BASED ON BIDIRECTIONAL FLUID-STRUCTURE COUPLING - LI Jin Yang; WANG JunLi; LEI Shuai; FENG YuRu; DU TianWei (Jixie qiangdu)
Based on the Miner linear cumulative damage theory and the finite element analysis method, the fatigue life of the wing with high aspect ratio at different angles of attack was calculated.Firstly, based on the N-S equation, the displacement, stress and strain of the wing structure in cruise state are solved by using the bidirectional fluid-structure coupling method.Secondly, the fatigue life of the wing structure is analyzed, and the fatigue life of the wing structure at the weak position and different angles of attack is obtained.The results show that the fatigue weakness of the wing with high aspect ratio tends to occur at the leading edge and the wing root, and the life of the leading edge increases from the wing tip to the wing root along the wing span.The life of the wing is closely related to the change of Angle of attack and airfoil parameters, and there is generally a maximum life Angle of attack under a given flight condition.